2022
DOI: 10.1111/joim.13466
|View full text |Cite
|
Sign up to set email alerts
|

Is acid suppression associated with the increased length of stay in diabetic ketoacidosis patients? A nationwide analysis

Abstract: Background Diabetic ketoacidosis (DKA) patients present with low serum bicarbonate (HCO3−${\rm{HCO}}_{3}^{-} $), and an increase in its level to ≥15 mEq/L is considered one of the criteria for DKA resolution. Both proton pump inhibitors and histamine‐2 receptor antagonists inhibit downstream functioning of H+/K+ ATPase in the gastric parietal cells, which results in the decreased secretion of HCO3−${\rm{HCO}}_{3}^{-} $ into the bloodstream. Objectives We aimed to introduce the hypothesis that DKA patients on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…This translates into an increased risk of developing DKA, or its recurrence, as shown in this study. Similarly, it is evident from the literature that young patients with diabetes tend to have a longer LOS in DKA admissions [ 8 ]. Therefore, young patients with diabetes, mainly newly diagnosed, should be the target population to address the rising healthcare resource utilization issues concerning DKA.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This translates into an increased risk of developing DKA, or its recurrence, as shown in this study. Similarly, it is evident from the literature that young patients with diabetes tend to have a longer LOS in DKA admissions [ 8 ]. Therefore, young patients with diabetes, mainly newly diagnosed, should be the target population to address the rising healthcare resource utilization issues concerning DKA.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies linked a high comorbidity burden with the development of DKA; however, data are limited regarding the effect of a high comorbidity burden on LOS in DKA admissions [ 28 ]. A recent study published in 2022 also reported an association of higher CCI with prolonged LOS in DKA patients [ 8 ]. It has shown clinical significance in predicting various diseases’ short-term and long-term clinical outcomes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations